Evaluation of Alvarado score and appendicitis inflammatory response score as diagnostic tools for acute appendicitis - Hassan, Mohamed; Jeilani, Milad; Saad, Ahmed A.; Iqbal, Sheeraz; Boshnaq, Mohamed (International Surgery Journal, 2022)
Background: The study aims to evaluate the diagnostic accuracy of AIR and Alvarado scores for acute appendicitis cases. Methods: We conducted a retrospective study with 73 patients to compare the efficacy of the appendicitis inflammatory response (AIR) score with the Alvarado score in the diagnosis of acute appendicitis from January 2021 to March 2021. The study included all consecutive patients referred with suspected appendicitis or acute RIF pain, to the surgical unit at Tunbridge Wells Hospital. Results: Based on histopathology findings of 73 patients, 59 (80.8%) patients had acute appendicitis. Using the AIR score, 5 (8.5%) patients scored high, 41 (69.5%) scored moderate, and 13 (22.0%) scored low in the histologically-positive group. In the histology-negative group, none (0.0%) scored high, 2 (14.3%) scored moderate, and 12 (85.7%) scored low, with only 2 patients being false positives. The correlation between the AIR score and histopathology results was thus highly significant (p value=0.000). Using the Alvarado score, in the histology-positive group, 33 (55.9%) scored high, 17 (28.8%) moderate and 9 (15.3%) low. In the histology-negative group, 2 (14.3%) patients scored high, 6 (42.9%) scored moderate, and 6 (42.9%) patients scored low. 8 patients were false positives. We found a significant correlation between the Alvarado score and histopathology results (p value=0.011). The sensitivity of the AIR and Alvarado scores were 77.97% and 67.80% respectively and the specificity was 85.71% and 78.57% respectively. Conclusions: The AIR score had higher specificity, sensitivity, positive predictive value, and a lower rate of false positives.